Treatment of patients with Waldenström macroglobulinaemia: clinical practice update from the Myeloma Foundation of Australia Medical and Scientific Advisory Group. Issue 4 (5th April 2023) - Talaulikar, Dipti; Joshua, Douglas; Ho, Phoebe Joy; Gibson, John; Quach, Hang; Gibbs, Simon; Ling, Silvia; Ward, Christopher; Augustson, Bradley M.; Trotman, Judith; Harrison, Simon J.; Tam, Constantine S.; et al.
Abstract: Waldenström macroglobulinaemia (WM) is an indolent B‐cell malignancy characterised by the presence of IgM paraprotein, bone marrow infiltration by clonal small B lymphocytes with plasmacytic differentiation and the MYD88 L265P mutation in >90% of cases. Traditionally, WM has been treated with chemoimmunotherapy. Recent trials have demonstrated the efficacy and safety of Bruton tyrosine kinase inhibitors in WM, both as monotherapy and in combination with other drugs. There is emerging evidence on the use of other agents including B‐cell lymphoma 2 inhibitors and on the treatment of rare presentations of WM. In this update, the Medical and Scientific Advisory Group of Myeloma Australia reviews the available evidence on the treatment of WM since the last publication in 2017 and provides specific recommendations to assist Australian clinicians in the management of this disease.